Guild-specific patterns of species richness and host specialization in plant-herbivore food webs from a tropical forest - Novotny, Vojtech; Miller, Scott E; Baje, Leontine; Balagawi, Solomon; Basset, Yves; Cizek, Lukas; Craft, Kathleen J; Dem, Francesca; Drew, Richard A I; Hulcr, Jiri; Leps, Jan; Lewis, Owen T; et al. (The Journal of animal ecology, 2010)
1. The extent to which plant-herbivore feeding interactions are specialized is key to understand the processes maintaining the diversity of both tropical forest plants and their insect herbivores. However, studies documenting the full complexity of tropical plant-herbivore food webs are lacking. 2. We describe a complex, species-rich plant-herbivore food web for lowland rain forest in Papua New Guinea, resolving 6818 feeding links between 224 plant species and 1490 herbivore species drawn from 11 distinct feeding guilds. By standardizing sampling intensity and the phylogenetic diversity of focal plants, we are able to make the first rigorous and unbiased comparisons of specificity patterns across feeding guilds. 3. Specificity was highly variable among guilds, spanning almost the full range of theoretically possible values from extreme trophic generalization to monophagy. 4. We identify guilds of herbivores that are most likely to influence the composition of tropical forest vegetation through density-dependent herbivory or apparent competition. 5. We calculate that 251 herbivore species (48 of them unique) are associated with each rain forest tree species in our study site so that the ∼200 tree species coexisting in the lowland rain forest community are involved in ∼50,000 trophic interactions with ∼9600 herbivore species of insects. This is the first estimate of total herbivore and interaction number in a rain forest plant-herbivore food web. 6. A comprehensive classification of insect herbivores into 24 guilds is proposed, providing a framework for comparative analyses across ecosystems and geographical regions.
Keywords: rostliny; Animals; stromy; Plants; tropické klima; stravovací zvyklosti; biodiverzita; Papua Nová Guinea; zvířata; Food Chain; potravní řetězec; Trees; hmyz; Feeding Behavior; Tropical Climate; Papua New Guinea; Insecta; Biodiversity